An empirical study of clone detection in MATLAB/Simulink models. (2018) - Rattan, Dhavleesh; Bhatia, Rajesh; Singh, Maninder
Complex systems consisting of millions of components are very difficult to develop and manage. Thus model driven development has become an essential development paradigm. But very large scale models suffer from unexpected overlaps of parts. The overlapped and copied fragments in models are known as model clones which increase maintenance cost and resource requirements. Recent research has shown the presence of clones in MATLAB/Simulink models. To gain better understanding, we have conducted an in-depth empirical study on 18 MATLAB/Simulink models using ConQAT, an open source clone detection framework. Our study shows that there is a significant cloning in models and find out some interesting patterns of clones which are significant to improve maintenance.